Rawls weltweit - Müller-Plantenberg, Urs (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2000)
Rawls‘ Theory of justice is related to a „closed“ society. His theory is discussed under the conditions of globalization, where the world society is the only useful meaning of a closed society. But insofar societies are organised in different states, people have to regard the needs of „outsiders“, if they want to practice a minimum of justice.